2009
DOI: 10.4018/jossp.2009070105
|View full text |Cite
|
Sign up to set email alerts
|

A Cost Model of Open Source Software Adoption

Abstract: A limited budget for IT may lock public bodies in obsolete inefficient solutions slowing down their process of innovation. Various actions of estimating, controlling, and reducing IT costs have been already performed at national and European levels and Open Source Software (OSS) has been often pointed as a promising alternative that may also render public services and the underlying business processes more transparent and accessible to citizens. In this chapter, we propose a model of cost of a migration to OSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The search string in their SLR study 23 does not include the word "quality" but the terms of "adoption model," "evaluation model," and "selection model." Therefore, in addition to quality evaluation models, that SLR study 23 also revealed different models for OSS, such as adoption cost models, 93 risk models, 94 and etc. Also, that SLR revealed studies that do not propose models and that are only related to software adoption, for example, Heili and Assar, 95 because of their search string.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The search string in their SLR study 23 does not include the word "quality" but the terms of "adoption model," "evaluation model," and "selection model." Therefore, in addition to quality evaluation models, that SLR study 23 also revealed different models for OSS, such as adoption cost models, 93 risk models, 94 and etc. Also, that SLR revealed studies that do not propose models and that are only related to software adoption, for example, Heili and Assar, 95 because of their search string.…”
Section: Related Workmentioning
confidence: 99%
“…The number of models examined in their SLR study 23 (35) is higher than the one (26) in our SLR study because the main focus of the models in that SLR study is not “quality,” as can be understood from its search string given in the table. The search string in their SLR study 23 does not include the word “quality” but the terms of “adoption model,” “evaluation model,” and “selection model.” Therefore, in addition to quality evaluation models, that SLR study 23 also revealed different models for OSS, such as adoption cost models, 93 risk models, 94 and etc. Also, that SLR revealed studies that do not propose models and that are only related to software adoption, for example, Heili and Assar, 95 because of their search string.…”
Section: Related Workmentioning
confidence: 99%
“…Other factors found relevant in complementary studies are the unfamiliarity of customers with FLOSS vendors' relationships, and the need to adapt corporate governance and architecture (Holck et al, 2005). The complex interrelations between multiple individual, technical, organizational, and environmental factors, including total cost of ownership (Russo and Succi, 2009), external market support have also been considered as relevant (Morgan and Finnegan, 2007).…”
Section: Adoption Of Floss In Public Organizationsmentioning
confidence: 99%